On the Need to Include Critical Pedagogy of the Latin American Kind in the Public Education System of Costa Rica - Solís Vargas, Yors Guillermo (2018)
The following essay is about the need for including critical pedagogy of Latin American origin as one of the main principles in the public educational system of Costa Rica. Hence, from the author´s perspective, teaching in this country has been dominated by European models, which however correct at the time of being implemented in this context, they lack the critical, ethical, aesthetic and political approach that can be strictly provided by a Latin American critical pedagogy standpoint.